Priority directions and prospects of cooperation of the Republic of Kazakhstan with South Korea - А.К. Майкибаева; К.М. Ильясова (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
In this article, from the foreign policy point of view, the evolution of cooperation between the Republic of Kazakhstan and South Korea in the post-Soviet period is considered. The authors conduct a comprehensive analysis of the economic relations of Kazakhstan not only with South Korea, but also with other foreign countries. At present, it is accepted in the world community that even the largest and the most developed countries cannot independently carry out technological and economic progress and create conditions for the efficient production of all necessary goods and services without any relations with other countries. Such tasks can be successfully solved only through international cooperation. International relations of Kazakhstan play an important role in its development as an independent sovereign state. Also considered are the stages of economic development of Kazakhstan over the past decades, relevant issues of a market economy, and features of the socio-economic development of the two republics. The main directions of Kazakhstan-Korean cooperation were identified. The results of the favorable influence of South Korea on the development of Kazakhstan are being summed up.